Is Multiple Pregnancy Really a Risk Factor? The Results of Fetal Echocardiography in a Tertiary Care Center - Tülay Demircan; Barış Güven; Ali Rahmi Bakiler; Halil Gürsoy Pala; Ayşe Şimşek; Nazmi Narin; Cem Karadeniz (Galenos Publishing House, 2022)
Objective: The aim of this study was to analyze the frequency and results of congenital heart defects (CHD) in multipl pregnancies by fetal echocardiography. Among these, to evaluate critical congenital heart diseases such as hypoplastic left heart syndrome, interrupted aorta, and pulmonary atresia etc that require care in a tertiary center. Method: This retrospective cohort study was conducted in pregnant women who admitted for fetal echocardiography. The data of the pregnancy were obtained retrospectively from the hospital records. A total of 9,440 pregnant women were enrolled in this study between January 2016 and September 2019. Two hundred and forty-one of them were multiple pregnancies (232 twins, 7 triplets and 2 quadruplets). Results: Congenital heart disease rate was 4.31% in singleton pregnancies and 8.7% in multiple pregnancies. The prevalence of CHD was significantly higher in multipl pregnancies (p=0.05). There was no statistically significant difference between the two groups with respect to rate of critical congenital heart disease (p=0.32). Conclusion: Multiple pregnancies had increased congenital heart defect risk compared with singleton. Therefore, it is important to refer for fetal echocardiography when necessary. Fetal echocardiography is routinely recommended in high-risk pregnancies such as monocarionic twin pregnancies. However, in pregnant women without risk factors for CHD is also seen. Postnatal follow-up of congenital heart disease is important, and early diagnosis of these diseases with fetal echocardiography is important.